Improving skin color accuracy in DLP-based 3D reconstruction (2024)
Color accuracy is crucial in several domains such as biomedical imaging, cosmetics, and multimedia. Digital Light Processing (DLP) with LEDs has increasingly become a popular lighting source in 3D scanning systems. Although DLP provides advantages in 3D reconstruction, it poses challenges in maintaining color accuracy. Our research focused on using hybrid lighting to improve the color accuracy of DLP-based 3D sensing systems. We developed an empirical dataset featuring skin tones captured under multiple lighting environments, including variations in indoor ambient lighting. Through qualitative and quantitative evaluations of color differences, we conclude that including auxiliary lighting with DLP is beneficial for color accuracy, particularly in biomedical imaging and other applications in which color accuracy is essential.